Solitary Peripheral Osteoma of the Angle of the Mandible - Kapil Kshirsagar; Kalyani Bhate; Vivek Pawar; S. N. SanthoshKumar; Supriya Kheur; Shrikant Dusane (Case Reports in Dentistry)
Solitary peripheral osteoma is a benign, slow-growing osteogenic tumor arising from craniofacial bones such as the sinus, temporal, or jaw bones but rarely originating from the mandible. Osteoma consists of compact or cancellous bone that may be of peripheral, central, or extraskeletal type. Peripheral osteoma arises from the periosteum and is commonly a unilateral, pedunculated mushroom-like mass. Solitary peripheral osteomas are characterized by well-defined, rounded, or oval radiopaque mass in the computed tomography. Although multiple osteomas of the jaws are a hallmark of Gardner’s syndrome (familial adenomatous polyposis), nonsyndromic cases are typically solitary. Herein, we report a rare case of solitary peripheral osteoma of the angle of the mandible in a 27-year-old female with clinical, radiologic, and histopathologic findings.